2020
DOI: 10.2174/1874364102014010001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal Limiting Membrane Peeling on Macular Structure and Metamorphopsia Scores in Idiopathic Epiretinal Membrane Surgery

Abstract: Backgrounds and Objective: Pars Plana Vitrectomy (PPV) and epiretinal membrane (ERM) peeling is the standard surgical procedure of ERM surgery. However, the effect of adding Internal Limiting Membrane (ILM) peeling to the standard surgery on macular function and structure remains still controversial. This study was aimed at investigating the effect of ILM peeling on the macular function and structure in idiopathic ERM surgery. Method: Thirty-six eyes of 34 patients were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…In this subgroup, 11 studies reported on one or more outcomes comparing eyes receiving PPV with and without ILM peel, where studies included patients receiving simultaneous phacoemulsification [15,16,[24][25][26][27][28][29][30][31][32]. All outcomes were consistent with the primary analysis, except for the outcomes described herein.…”
Section: Subgroup Analysis: Simultaneous Phacoemulsificationmentioning
confidence: 98%
See 4 more Smart Citations
“…In this subgroup, 11 studies reported on one or more outcomes comparing eyes receiving PPV with and without ILM peel, where studies included patients receiving simultaneous phacoemulsification [15,16,[24][25][26][27][28][29][30][31][32]. All outcomes were consistent with the primary analysis, except for the outcomes described herein.…”
Section: Subgroup Analysis: Simultaneous Phacoemulsificationmentioning
confidence: 98%
“…A total of 7,686 studies underwent title and abstract screening, 395 underwent full-text screening and 19 studies reporting on 1,291 eyes at baseline were included in our meta-analysis (Fig. 1) [3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Six included studies were RCTs [17,23,[29][30][31][32], and 13 were observational studies [3,15,16,[18][19][20][21][22][24][25][26][27][28].…”
Section: Study Selection and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations